Gambaran Penerapan SOP Panen Pada Karyawan Pemanen Sawit Di PT. Tasma Puja - Rudi Cahyadi; Dessyka Febria; Rizki Rahmawati Lestari (Excellent Health Journal, 2025)
Work accidents are the main challenge that affects employee safety and productivity in the palm oil plantation sector in the harvesting section which still often occurs, due to the lack of implementation of Standard Operating Procedures (SOP) for harvesting. The purpose of this study was to describe the implementation of SOP for harvesting employees, with a focus on work safety and efficiency of the harvesting process. The study used a descriptive design with a quantitative approach with a sample of 129 palm oil harvesting employees selected using a simple random sampling technique. Primary data were collected through direct observation using observation sheets that included indicators of SOP implementation. Secondary data were obtained from company documents. Data analysis was carried out univariately to describe the level of SOP implementation. The results showed that the majority of employees 69% had implemented the harvesting SOP properly, while 31% had not fully complied with the procedure. Good implementation of SOPs supports increased work safety, efficiency of the harvesting process, and productivity. It is recommended that respondents be more disciplined in implementing the harvesting SOP, including consistent use of PPE and proper implementation of work procedures at every stage of the harvesting process. Active participation in work safety training held by the company is also expected to increase awareness and understanding of the importance of working according to SOP. By complying with SOPs, employees can protect themselves from the risk of accidents, while contributing to increased work productivity and the sustainability of company operations